Saving Arcadia : A Story of Conservation and Community in the Great Lakes - Shumaker, Heather (Book collections on Project MUSE., 2017)
This is the story of a small band of determined townspeople and how far they went to save beloved land and endangered species from the grip of a powerful corporation in the Arcadia Dunes. This is a narrative with roots as deep as the trees the community is trying to save, something set in motion before the author was even born. And yet, Shumaker gives a human face to the changing nature of land conservation in the twenty-first century. The result is a triumph of community that includes working farms, local businesses, summer visitors, year-round residents, and a network of land stewards. A work of creative nonfiction, Saving Arcadia is the adventurous tale of everyday people fighting to reclaim the land that has been in their family for generations. It explores ideas about nature and community, and anyone from scholars of ecology and conservation biology to readers of naturalist writing can gain from Arcadia's story.